2021
DOI: 10.1186/s12887-020-02468-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hand-forearm anthropometric components in assessing handgrip and pinch strengths of school-aged children and adolescents: a partial least squares (PLS) approach

Abstract: Background The purpose of this study was to examine the influence of hand-forearm anthropometric dimensions on handgrip and pinch strengths among 7–18 years children and adolescents and to investigate the extent to which these variables can be used to predict hand strength. Methods Four types of hand strengths including handgrip, tip to tip, key, and three-jaw chuck pinches were measured in 2637 healthy children and adolescents (1391 boys and 1246 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The order of the muscles tested, the standardized positions, and hand-held dynamometer placement for each muscle group were based on previous reports and are described in Table 1 ( Daloia et al, 2018 ; Escobar et al, 2017 ; Hébert et al, 2011 , 2015 ). The maximum isometric grip strength of the extrinsic and intrinsic hand muscles was assessed with HGD using a calibrated hand-grip dynamometer (Jamar 5030J1, Sammons Preston Rolyan, Bolingbrook, IL, USA) according to the recommendation of the American Society of Hand Therapists widely used in the scientific literature ( Rauch et al, 2002 ; Rostamzadeh et al, 2021 ). The handle was adjusted so that the line of the subject’s proximal interphalangeal joints rested exactly on top of the adjustable handle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The order of the muscles tested, the standardized positions, and hand-held dynamometer placement for each muscle group were based on previous reports and are described in Table 1 ( Daloia et al, 2018 ; Escobar et al, 2017 ; Hébert et al, 2011 , 2015 ). The maximum isometric grip strength of the extrinsic and intrinsic hand muscles was assessed with HGD using a calibrated hand-grip dynamometer (Jamar 5030J1, Sammons Preston Rolyan, Bolingbrook, IL, USA) according to the recommendation of the American Society of Hand Therapists widely used in the scientific literature ( Rauch et al, 2002 ; Rostamzadeh et al, 2021 ). The handle was adjusted so that the line of the subject’s proximal interphalangeal joints rested exactly on top of the adjustable handle.…”
Section: Methodsmentioning
confidence: 99%
“…The handle was adjusted so that the line of the subject’s proximal interphalangeal joints rested exactly on top of the adjustable handle. Participants were seated with their arms by their sides, with elbows flexed 90° (without touching the trunk), forearms in a neutral position, and the wrists held between 0°–30° dorsiflexion and between 0°–15° ulnar deviation ( Rauch et al, 2002 ; Rostamzadeh et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the correlation analysis results are contradictory in studies that included healthy children and adolescents (22-24, 32, 34), elderly Malaysians (20), hospitalized Portuguese patients (3), healthy Caucasian adults (25-28), healthy Indian collegiate population (33) and healthy Brazilian adults (21). Some studies reported that the correlation coefficient between HGS and height is larger than that between HGS and weight (3,20,22,(25)(26)(27)(28)34). While other studies reported that the correlation coefficient is smaller (12, 29-31) or similar (10,32,33).…”
Section: Weight Is More Correlated With Hand Grip Strength Than Heightmentioning
confidence: 99%
“…Previous studies have shown contradictory results on the correlation coefficient between HGS and height and weight. Some studies reported that the correlation coefficient between HGS and height is larger than that between HGS and weight (3,(20)(21)(22)(23)(24)(25)(26)(27)(28). In other studies, the correlation coefficient between HGS and height is, on the contrary, smaller than that between HGS and weight (12, [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Pinch strength has been measured in a variety of ways from 3 to 10 seconds [16,17]. Handgrip strength has been measured in 3 to 5 seconds, and it has been reported that the maximum value can be measured within 5 seconds [12].…”
Section: Pinch Strength Measurement Timementioning
confidence: 99%